2014
DOI: 10.1371/journal.pone.0094199
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Campanuloideae (Campanulaceae) with Emphasis on the Utility of Nuclear Pentatricopeptide Repeat (PPR) Genes

Abstract: BackgroundThe Campanuloideae (Campanulaceae) are a highly diverse clade of angiosperms found mostly in the Northern Hemisphere, with the highest diversity in temperate areas of the Old World. Chloroplast markers have greatly improved our understanding of this clade but many relationships remain unclear primarily due to low levels of molecular evolution and recent and rapid divergence. Furthermore, focusing solely on maternally inherited markers such as those from the chloroplast genome may obscure processes su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 59 publications
9
60
0
Order By: Relevance
“…Recent studies conducted within the Campanulaceae family have made significant progresses toward a robust phylogenetic hypothesis of the group (Crowl et al., ; 2016). These authors concluded that previous studies including ITS have shown significant limitation in resolving species level relationships and providing accurate information on the placement of several genera (e.g., Jasione and Musschia ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies conducted within the Campanulaceae family have made significant progresses toward a robust phylogenetic hypothesis of the group (Crowl et al., ; 2016). These authors concluded that previous studies including ITS have shown significant limitation in resolving species level relationships and providing accurate information on the placement of several genera (e.g., Jasione and Musschia ).…”
Section: Discussionmentioning
confidence: 99%
“…Six chloroplast (cpDNA) regions were amplified: atpB , matK , petD , rbcL , trnL‐F (Crowl et al., ) and psbA‐trnH (Kress, Wurdack, Zimmer, Weigt, & Janzen, ); and one nuclear region (ITS) with the primers of Douzery et al. ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenies were inferred using maximum likelihood (ML) and Bayesian inference as implemented in RAxML 8.0 (Stamatakis, ) and B east 2.1.3 (Bouckaert et al ., ). Four calibration points were used to estimate divergence times: the fossil seed of † Campanula paleopyramidalis as a minimum age constraint of 16 Myr for the most recent common ancestor of C. pyramidalis and C. carpatica (Cellinese et al ., ; Crowl et al ., ); a geological maximum age constraint of 29.8 Myr, which corresponds to the age of the Kure atoll, the oldest emerged island of the Hawaiian Ridge (Clague, ), for the crown group of the endemic Hawaiian clade, encompassing c . 125 spp.…”
Section: Methodsmentioning
confidence: 99%
“…The annual and perennial Campanula taxa grow in various habitats, such as meadows, grasslands, garrigues, woodlands, and mainly in rupestrian stands (Kovačić 2004;Roquet et al 2008). The high variability of the morphological traits provided numerous classification proposals (De Candolle 1830;Boissier 1875;Gadella 1966a, b;Contandriopoulos 1984;Kolakovsky 1994), but none of them reflect the phylogenetic relationships recently obtained with molecular data, which showed that Campanula and many closely related genera are not monophyletic (Eddie et al 2003;Park et al 2006;Roquet et al 2008Roquet et al , 2009Borsch et al 2009;Cellinese et al 2009;Haberle et al 2009;Mansion et al 2012;Crowl et al 2014). Nevertheless, molecular data identified several wellsupported monophyletic groups within Campanula, e.g., the garganica clade (Park et al 2006;Frajman and Schneeweiss 2009;Bogdanović et al 2014a, b), the fragilis clade, the pyramidalis clade (LakuĹĄić et al 2013), and closely related lineages, e.g., Phyteuma ).…”
Section: Introductionmentioning
confidence: 99%